Penerimaan Diri Wanita Infertilitas - Nora Nurhadhani; Ella Suzanna (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
Infertility is a failure to obtain a pregnancy after 12 months or more having sexual intercourse on a regular basis without the use of a contraceptive device. Infertility cases are expected to increase annually. Infertility has an impact on the lives of women who experience it. Self-acceptance is needed to help infertile woman be able to accept all the conditions by not criticizing and accepting the views of oneself and other against them. The purpose of this research is to describe the depiction of self-acceptance in infertility women in Paya Gaboh. This research uses qualitative methods with a phenomenological approach. The procedure of taking the respondent using purposive sampling technique of 3 person is a woman who experienced primary infertility who lived in Paya Gaboh. Research data is collected through interviews, observations and documentation. Analysis of data on research using theme data analysis. The result showed that the three respondents had reached a stage of self-acceptance influenced by different factors and stages. Each respondent’s self acceptance is influenced by social support, religiality, and self-understanding. While the self-acceptance stages that are passed by respondents are the level of denial, anger stage, depression stage, and acceptance stage.